Seed viability and vigour in naturally aged seeds of coriander (Coriandrum sativum) - KUMAR, VIPESH; VERMA, SHER SINGH; VERMA, URMIL; KUMAR, AXAY (The Indian Journal of Agricultural Sciences, 2015)
In the present investigation, three seed lots of eight varieties/genotypes, viz. DH 224, DH 226, DH 242, DH 259, DH 294, DH 296 (advance genotypes) and DH 228 (Hisar Bhoomit) and Hisar Anand (released varieties) of coriander were subjected to study the effect of natural ageing on different seed quality parameters. All the seed lots were analyzed for standard germination test (%), root length (cm), shoot length (cm), seedling dry weight (mg), seedling vigour index-I, seedling vigour index-II, accelerated ageing test (%), electrical conductivity (mS/cm/seed) of seed leachates, seed density (g/cc), dehydrogenase activity test (OD/g/mL), field emergence index and field establishment (%). Results revealed that all the varieties/genotypes showed the germination percentage above the Minimum Seed Certification Standards (60%) in Lot-A (½ year old seed) and Lot-B (1½ years old seed). Standard germination (%), seedling length (cm), seedling dry weight (mg), seedling vigour index-I &II, accelerated ageing test (%), dehydrogenase activity test (OD/g/mL), field emergence index and field establishment (%) decreased significantly and progressively as the ageing period increased. The electrical conductivity was negatively and significantly correlated with all seed viability and vigour parameters. Results also revealed that viability and vigour of seeds declined with faster rate in Lot-C (2½ years old seed). Among all the varieties/genotypes, genotypes DH 224 and DH 228 were found most promising for various parameters of viability and vigour.